Perancangan dan Penerapan 5S pada Laboratorium Proses Manufaktur Universitas Kristen Petra - Silvester Chung (Jurnal Titra, 2019)
The Manufacturing Process Laboratory is used for Manufacturing Process Practicum for students of Mechanical Engineering Study Program and Industrial Engineering Study Program. The problem faced by the Manufacturing Process Laboratory is that the laboratory is still not clean, has not been well organized and has not yet cultivated the 5S method, so that operator performance cannot be maximized. Efforts that can be made in improving laboratory performance are by cultivating the 5S method, namely sorting, structuring, cleaning, maintenance, and civilizing. The design and implementation of 5S carried out in this Final Project is to clean the laboratory, tidy up the equipment in the laboratory, make a storage place for equipment and make 5S aids in the form of hygiene posters, 5S posters, and 5S videos. The final results of the implementation of 5S laboratories become cleaner, neater, and more convenient to use and work activities run better.